A Simple and Accurate Interpretation Method of In Situ Stress Measurement Based on Rock Kaiser Effect and Its Application. (7th June 2018) - Zhao, Kang; Gu, Shuijie; Yan, Yajing; Zhou, Keping; Li, Qiang; Zhu, Shengtang
Abstract : Many deep underground excavation practices show that the size and distribution of in situ stress are the main factors resulting in the deformation and instability of the surrounding rock structure. The in situ stress measured by the Kaiser effect of rock is used by engineers because of its economy and convenience. However, due to the lack of quantitative judgment basis in determining the Kaiser point position, there is a large artificial error in the practical application. In response to the problem, this study systematically investigates the characteristics of rock acoustic emission curve on the basis of the fractal theory and establishes an accurate and simple interpretation method for determining the Kaiser point position. The indoor rock acoustic emission test was carried out by drilling a rock sample at a mine site. By using the conventional tangent method, the cumulative ringing count rate-time-stress curve of rock acoustic emission is analyzed to preliminarily determine the time range of Kaiser point appearance. Considering that the fractal dimension of the rock Kaiser point is lower than the adjacent point, the minimum point of the fractal dimension of this time range can be determined from the fractal dimension-time-stress curve. Such determined point is the Kaiser point. The size of the in situ stress is calculated using an analytical method. Based on the value of the in situ stress, the distribution of the in situ stress in the mining area is further analyzed using the geological structure of the mine. The maximum principal stress is 19.38 MPa, with a direction of N (30°-40°) E, and the minimum principal stress is 8.02 MPa with a direction of N (50°-60°) W. The maximum and minimum principal stresses are approximately in the horizontal plane. The intermediate principal stress is 11.73 MPa in vertically downward. These results are basically consistent with the distribution statistical law of the measured in situ stress fields in the world. The results presented in the study could provide a reference for the later mining, stability evaluation, and support of the surrounding rock.